2017
DOI: 10.3390/nu9030273
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Assessing Diet with a Mobile Food  Record for Adolescents and Young Adults with  Down Syndrome

Abstract: Technology-based methods for assessing diet in those with disability remains largely unexplored. The aim was to assess the feasibility of assessing diet with an image-based mobile food record application (mFR) in 51 adolescents and young adults with Down syndrome (PANDs). Adherence was also assessed with the instruction to include a fiducial marker object in the before and after eating images. The PANDs sample completed a four-day mFR and results were compared with a sample of young adults from the Connecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Requesting the use of both methods for a total of six days within a two-week timeframe was feasible for both child and parent schedules. This expanded on what was reported by Bathgate and colleagues [ 13 ] who tested the feasibility of using the TADA mFR™ in a slightly older sample of individuals with Down syndrome. In their study, 86% (51/59) of the sample successfully recorded nutritional intake with the mFR™ for a minimum of two days [ 13 ], whereas 100% of the sample in the current study successfully collected both the image recordings for the mFR™ and the 24 HR-FT for a total of six days.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Requesting the use of both methods for a total of six days within a two-week timeframe was feasible for both child and parent schedules. This expanded on what was reported by Bathgate and colleagues [ 13 ] who tested the feasibility of using the TADA mFR™ in a slightly older sample of individuals with Down syndrome. In their study, 86% (51/59) of the sample successfully recorded nutritional intake with the mFR™ for a minimum of two days [ 13 ], whereas 100% of the sample in the current study successfully collected both the image recordings for the mFR™ and the 24 HR-FT for a total of six days.…”
Section: Discussionmentioning
confidence: 66%
“…This expanded on what was reported by Bathgate and colleagues [ 13 ] who tested the feasibility of using the TADA mFR™ in a slightly older sample of individuals with Down syndrome. In their study, 86% (51/59) of the sample successfully recorded nutritional intake with the mFR™ for a minimum of two days [ 13 ], whereas 100% of the sample in the current study successfully collected both the image recordings for the mFR™ and the 24 HR-FT for a total of six days. Notable differences between these studies were that the sample in the current study was smaller, younger, and included children with spina bifida and without developmental disabilities.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, web-based 24-h recall methods such as the Automated Self-Administered 24-Hour Recall (ASA24) have been shown to be acceptable even among older adults [ 54 ], which holds promise for other technology-based assessment tools. Previous reviews have identified the need for training of participants when using many of these tools [ 14 ] and it maybe that these aspects require further development for specialist populations, although research suggests that some tools may be feasible in diverse community groups [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 studies described event-contingent mEMDA methods used in nutrition-related research [52][53][54][55][56][57][58][59][60][61]. Additional approach details were extracted from other related journal articles [43,[62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Summary Of Event-contingent Studiesmentioning
confidence: 99%